Reduction in Cigarettes per Day Prospectively Predicts Making a Quit Attempt: A Fine-Grained Secondary Analysis of a Natural History Study. Issue 5 (22nd March 2018) - Klemperer, Elias M; Hughes, John R; Naud, Shelly
Abstract: Introduction: Reducing cigarettes per day (CPD) aided by medication increases quit attempts (QA) among smokers not trying to quit. If this is due to reducing CPD per se, then a greater reduction should predict making a QA. Aims and Methods: In this secondary analysis, 132 smokers completed nightly calls to report CPD, intention to quit tomorrow, and QAs over 12 weeks. We provided no treatment. We identified episodes of reduction and tested whether (1) percent reduction in CPD, (2) absolute reduction in CPD, (3) duration of reduction, or (4) CPD on the final day predicted a QA immediately after a reduction episode. We tested this separately among reduction episodes that began with and without an intention to quit. Results: Among the 1179 episodes that began without intention to quit, all four measures of reduction predicted making a QA. Greater percent reduction, longer duration, and fewer CPD on the final day were retained in a multivariate model (all p < .05). Among the 85 episodes that began with intention to quit, greater percent reduction and greater absolute reduction predicted making a QA. Only mean percent reduction was retained in a multivariate model ( p < .001). Conclusions: Our results replicate and extend earlier studies by using fine-grained analyses and examining immediately proximal QAs in a sample of self-quitters. Findings suggest that reducing CPD per se increases the probability of a QA among smokers without intention to quit in a dose-related manner. Whether this is the case among smokers who intend to quit remains unclear. Implications: Reducing CPD appears to be an effective strategy to increase the probability of making a QA for the majority of smokers who do not intend to quit in the near future. However, our findings are mixed regarding the effectiveness of reducing among smokers who intend to quit. Clinical interventions and policies that promote reducing CPD are likely to be an effective way to increase QAs. Reduction may be especially helpful for smokers who have not responded to traditional advice to stop abruptly.